Effect of carbon nanotubes on friction and wear of a piston ring and cylinder liner system under dry and lubricated conditions - Zhinan Zhang; Jun Liu; Tonghai Wu; Youbai Xie (Friction)
Abstract This study involves the application of carbon nanotubes (CNTs) to a piston ring and cylinder liner system in order to investigate their effect on friction and wear under dry and lubricated conditions. Carbon nanotubes were used as a solid lubricant and lubricant additive in dry and lubricated conditions, respectively. Simulation and measurement of friction and wear were conducted using a reciprocating tribometer. Surface analysis was performed using a scanning electron microscope and an energy dispersive spectrometer. The results indicate that carbon nanotubes can considerably improve the tribological performance of a piston ring and cylinder liner system under dry sliding conditions, whereas improvement under lubricated conditions is not obvious. Under dry friction, the effective time of the CNTs is limited and the friction coefficient decreases with an increase in CNT content. Furthermore, the dominant wear mechanism during dry friction is adhesive.